Democracy, fundamental rights and public finance: a constitutionalist criticism of the Steuerle-Roeper Index - Tavares, Francisco Mata Machado (Revista de Investigações Constitucionais, 2021)
The article proposes to critically discuss the concept of fiscal democracy as operationalized by the means of the Steuerle-Roeper Index. It is assumed that the contemporary sociohistorical context comprises a scenario of crisis or decline of democracies, largely explained by the fiscal difficulties faced by the States. The Fiscal Democracy Index is discussed as a promising scientific contribution for the attribution of empirical tangibility to such a reality. However, a difficulty is identified concerning the non-consideration of fundamental rights as condition for the possibility of democratic politics. Finally, an example from the Brazilian constitutional system is presented in order to illustrate the article´s theoretical argument.